A Novel Combined Conjugate Therapeutic Cancer Vaccine, Recombinant EGF-CRM197, in Patients With Advanced Solid Tumors: A Phase I Clinical Study - Xiong, An-Wen; Fang, Jue-Min; Ren, Sheng-Xiang; Li, Wei; Wang, Jing; Zhao, Yu; Chen, Guo-You; Xu, Qing; Zhou, Cai-Cun (Frontiers in Oncology, 2021)
Introduction: The therapeutic cancer vaccine recombinant Epidermal Growth Factor (EGF)-CRM197 is a novel combined conjugate EGF with CRM197 as a carrier protein. Immunization with the EGF-CRM197 vaccine can induce high levels of neutralizing anti-EGF antibodies that inhibit EGF/ EGFR signaling and suppress growth of tumors. Herein, we characterize the humoral immune responses elicited by the recombinant EGF-CRM197 vaccine in patients with advanced solid tumors in a phase I clinical trial and assess the safety, tolerability, and immunogenicity of this vaccine (CTR20190473). Methods: A total of 16 subjects were enrolled. Under 6+3 design, patients in each dosing cohort were administrated subcutaneously at a dosage of 0.4 mg, 0.8 mg, and 1.6 mg, respectively. The patients received vaccinations for immune induction (once a week for 4 consecutive weeks) and booster vaccinations (once every 4 weeks). Safety evaluation was performed 1 week after the immune induction. Booster vaccination was given until the occurrence of disease progression, intolerance, withdrawal of informed consent by the patient, or negative result of anti-EGF test after two booster vaccinations. Results: Vaccination with EGF-CRM197 is safe and well-tolerated in patients with advanced solid tumors. Adverse reactions at the injection site were the most common adverse events (AEs) in recipients. No severe adverse reactions were observed. Vaccinated patients developed a robust neutralizing antibody response triggered by EGF-CRM197 that significantly reduced the levels of EGF in serum. For lung cancer patients who were super good antibody responders (sGAR) to EGF-CRM197, the median progress-free survival (PFS) was 4.83 months, significantly longer than that of the good antibody responder (GAR) patients with lung cancer whose median PFS was 2.10 months (P=0.0018). The median overall survival (OS) of GAR lung cancer patients was 10.67 months while the OS) for sGAR lung cancer patients was not reached until analysis was performed. The median follow-up of the sGAR lung cancer patients was 14.6 months. Conclusion: Our study demonstrates that the recombinant EGF-CRM197 therapeutic cancer vaccine can induce a good immune response in patients and is safe and well tolerated, which ensures further clinical development for extending the survival time of sensitive patients with advanced solid tumors.